Pembuatan Aplikasi Toko Thriftsans Berbasis Web Menggunakan PHP Dan MySQL - Indah Tri Handayani; Kusuma Hati; Muhammad Rio Pratama (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2023)
Thriftsans is a clothing store that offers a wide variety of clothing styles. Thriftsans stores have customers ranging from the middle class to the upper class, with an average of thirty customer visits per day. Currently the sales system used is still manual, causing obstacles for the company including manual sales reporting, lack of marketing reach around the thriftsans store area, customers having difficulty getting the latest product information and lack of opportunity to get new customers, this has an impact on the company's revenue which not increasing. Therefore a website was created that can provide convenience in selling clothing products using the programming language PHP and MySQL as the database. This website only contains clothing products sold by Thriftsans, product installation history and payment confirmation using the transfer method. This website can be accessed at www.thriftsans.thriftsans.xyz. This application can be run on a browser and can make it easier for business owners to market clothing products at Thriftsans stores and can make it easier for customers to purchase products because it can save time and make it easier for customers without having to come to the store in person, of course it is very helpful for customers who are busy working and during a pandemic like today. Keywords—Website, Ordering, PHP, MYSQL, Thriftsans Thriftsans adalah toko pakaian yang menawarkan berbagai macam gaya pakaian. Toko Thriftsans memiliki pelanggan mulai dari kelas menengah hingga kelas atas, dengan rata-rata tiga puluh kunjungan pelanggan per hari. Saat ini sistem penjualan yang digunakan masih manual sehingga menimbulkan kendala bagi perusahaan antara lain pelaporan penjualan secara manual, kurangnya jangkauan pemasaran di sekitar area toko thriftsans, pelanggan kesulitan mendapatkan informasi produk terbaru dan kurangnya kesempatan untuk mendapatkan pelanggan baru, hal ini berdampak pada pendapatan perusahaan yang tidak meningkat. Maka dari itu dibuatlah website yang dapat memberikan kemudahan dalam menjual produk pakaian dengan menggunakan bahasa pemrograman PHP dan MySQL sebagai databasenya. Website ini hanya berisi produk pakaian yang dijual oleh Thriftsans, riwayat pemasangan produk dan konfirmasi pembayaran menggunakan metode transfer. Website ini dapat diakses di www.thriftsans.thriftsans.xyz. Aplikasi ini dapat dijalankan pada browser dan dapat mempermudah pemilik usaha dalam memasarkan produk pakaian pada toko Thriftsans serta dapat mempermudah pelanggan dalam melakukan pembelian produk karena dapat menghemat waktu dan mempermudah pelanggan tanpa harus datang ke toko secara langsung, tentunya sangat membantu bagi pelanggan yang sibuk bekerja dan pada masa pandemi seperti saat ini. Kata Kunci—Website, Pemesanan, PHP, MySQL, Thriftsans